Sociabilités de jeunes filles dans l’œuvre de Gustave Flaubert - Éléonore Reverzy (Flaubert: Revue Critique et Génétique)
In this paper, we try to think about the isolation and the singularity of the young girl in the Flaubertian novel. Going through the pre-texts, we realise that this isolation was not so complete for Emma as for Félicité, and that Flaubert worked to de-socialise his character. Louise Roque, with the grace of a young wild beast, follows Emma in her rebellion.